Intracerebral Hemorrhage in the Oldest Old: A Population-Based Study (Vantaa 85+) - Tanskanen, Maarit; Mäkelä, Mira; Myllykangas, Liisa; Rastas, Sari; Sulkava, Raimo; Paetau, Anders (Frontiers in Neurology, 2012)
Aims: Very elderly subjects form the fastest growing population in the world. Most of the studies on intracerebral haemorrhage (ICH) have been carried out on younger patients. We aimed to investigate the prevalence and risk factors of ICH in the oldest old. Materials and methods: The brains of 300 autopsied individuals (248 females, 52 males, mean age at death 92  3.7 years) were investigated as part of the prospective population-based Vantaa 85+ study. After macroscopic investigation, the presence and extent of microscopic brain haemorrhages (MH) was analyzed by counting the number of iron containing macrophages (siderophages) in the Prussian blue stain. Deposits with > 5 siderophages were defined as MH+. Genotyping of apolipoprotein E (APOE) and the analysis of microscopic (MI) or larger infarctions and cerebral amyloid angiopathy (CAA) were performed using standardized methods. Regression analysis was used to predict the presence of ICH, with and without co-localized CAA, adjusted for age at death and gender. Results: The prevalence of macroscopic ICH was 2%, of large lobar haemorrhage (LH) and deep haemorrhage (DH) 1% for each, and of subarachnoid haemorrhage (SAH) 0.3%. 62% had MH and 15.3% MH+. 55.9% of subjects with MH and 81.2% of those with MH+ showed MH / MH+ and CAA in the same brain region (MHCAA and MH+CAA, respectively). MH was associated with none of the clinical, genetic or neuropathological conditions analyzed. The subjects with MH+, MHCAA and MH+CAA expressed the APOE ε4 allele (OR 3.681, 3.291, 7.522, respectively). Siderophages in MH+CAA co-localized with CAA and with two thirds of the MI in the tissue sections. Conclusion: Macroscopic ICH was rare in the very elderly. MH was frequent and clinically insignificant. MH+ was rare but closely related with APOE ε4 genotype and the presence of severe CAA and infarction. MH+ is the putative histological counterpart of the MH lesions visible in the MRI (microbleeds), either with or without CAA / MI